2022
DOI: 10.3389/fnagi.2022.975176
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine, inflammation, and central nervous system diseases

Abstract: Phosphatidylserine (PS) is an anionic phospholipid in the eukaryotic membrane and is abundant in the brain. Accumulated studies have revealed that PS is involved in the multiple functions of the brain, such as activation of membrane signaling pathways, neuroinflammation, neurotransmission, and synaptic refinement. Those functions of PS are related to central nervous system (CNS) diseases. In this review, we discuss the metabolism of PS, the anti-inflammation function of PS in the brain; the alterations of PS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 199 publications
1
11
0
Order By: Relevance
“…The phosphatidylserine is known to regulate various membrane-bound receptor proteins that play pivotal roles in synaptic signal transduction, synaptic refinement, and neuronal apoptosis. , Given the importance of PS in regulating normal brain function, several recent studies unfolded the dysregulated levels of PS in neuro diseases like Alzheimer’s disease, Parkinson’s disease, and depressive disorders. Some recent studies indicated the link between increased expression of anionic phospholipids (including PS) and neurodegenerative diseases ( e.g. , Parkinson’s disease) modulated by preferential interaction of α-synuclein (a neuronal protein responsible for vesicle trafficking) with these membrane lipids. , All this body of evidence may hint at the critical implication of PS and other negatively charged phospholipids (PG, PI, PA, etc. )…”
Section: Discussionmentioning
confidence: 99%
“…The phosphatidylserine is known to regulate various membrane-bound receptor proteins that play pivotal roles in synaptic signal transduction, synaptic refinement, and neuronal apoptosis. , Given the importance of PS in regulating normal brain function, several recent studies unfolded the dysregulated levels of PS in neuro diseases like Alzheimer’s disease, Parkinson’s disease, and depressive disorders. Some recent studies indicated the link between increased expression of anionic phospholipids (including PS) and neurodegenerative diseases ( e.g. , Parkinson’s disease) modulated by preferential interaction of α-synuclein (a neuronal protein responsible for vesicle trafficking) with these membrane lipids. , All this body of evidence may hint at the critical implication of PS and other negatively charged phospholipids (PG, PI, PA, etc. )…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proposed that disrupted endosomal trafficking by elevating endosomal PI3P and PI(3,5)P 2 due to inactive MTMR2 likely contributes to the demyelination of nerve cells (Bonneick et al ., 2005; Previtali et al ., 2007). Intriguingly, PtdSer is the main component of myelin sheath (Ma et al , 2022), and inhibition of PI4KA in Schwann cells reduces PM and total levels of PtdSer and PI4P, and induces aberrant myelination (Alvarez-Prats et al , 2018). Thus, in addition to disrupted endosomal trafficking by MTMR2 inactivation, it is plausible that the reduced PM levels of PtdSer and PI4P further contributes to the demyelination observed in Charcot-Marie-Tooth disease type 4B1.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PC supplementation demonstrated beneficial effects on intestinal inflammation in patients and in laboratory models [ 47 , 48 , 49 , 50 ]. Likewise, PS is regarded as beneficial for central nervous system health as was demonstrated in animal and human studies, and PS-containing supplements are widely available for everyday use [ 39 , 51 , 52 , 53 ]. Finally, PA can serve as a precursor in PLs biosynthesis, and it is commonly used by sportsmen to facilitate strength and muscle endurance as a mammalian target of rapamycin (mTOR) signaling pathway agonist [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%